Pengaruh Marketing Affiliate Terhadap Keputusan Pembelian(Studi Kasus pada E-commerce Shopee) - Hening Lintang Kinanthi; Aditya Bayu Kusuma (Teewan Journal Solutions, 2025)
Marketing is no longer just referring to traditional advertising and personal promotion. One of the digital marketing techniques that is currently trending is Affiliate Marketing. And Shopee is one of the e-commerce that uses affiliate marketing as one of its marketing activities. The rapid development of e-commerce platforms and social media in the use of Affiliate marketing has encouraged the author to conduct research to examine the factors of Affiliate marketing that can influence Purchasing decisions. For this reason, the title